Household Welfare Effects of Stress-Tolerant Varieties in Northern Uganda - Mwungu, Chris Miyinzi; Mwongera, Caroline; Shikuku, Kelvin Mashisia; Acosta, Mariola; Ampaire, Edidah L.; Winowiecki, Leigh Ann; Läderach, Peter R.D. (Springer, 2019)
This study assessed the adoption of stress-tolerant varieties and their effect on household welfare, measured by net crop income per capita in Nwoya District, Uganda. The stress-tolerant varieties were considered to be climate-smart because they stabilise and increase crop income in the presence of climatic shocks. However, the uptake of the stress-tolerant varieties was still low in northern Uganda, due to bad past experience in terms of the performance of other improved varieties. Using data from a random sample of 585 households, a logistic model was estimated to assess the drivers for adoption of stress-tolerant varieties. In addition, a propensity score matching model was employed to assess causal effects. The second model was estimated because it controls for unobserved heterogeneity caused by self-selection bias. Results showed that adoption of stress-tolerant varieties was positively influenced by household size, access to information from non-governmental organizations (NGOs), the perception of future climate change, the number of years an individual had lived in the village, and the number and type of assets owned as an indicator of household well-being. Average treatment effect from results showed that stress-tolerant varieties can increase crop income within a range of United States Dollars (USD) 500–864 per hectare per year, representing an 18–32% increase in crop income. The findings offer justification for scaling up stress tolerant varieties among smallholder farmers in northern Uganda to improve their welfare.